VD_FINDINFO HC / 2019 / 8 vom 1. Februar 2019 - VD Tribunal cantonal (2019)
DROIT DE GARDE, GARDE ALTERNÉE, OBLIGATION D'ENTRETIEN, ENFANT, CONJOINT | 176 al. 1 ch. 1 CC, 276 CC, 285 CC, 298 al. 2ter CC